Once again on Pl. Symp. 172a* - Carmen Hernández García (Ágora)
This paper aims to discuss yet once more the extensively commented opening of Plato’s Symposium. Some scholars have readily acknowledged that the second summon οὗτος Ἀπολλόδωρος was intended to be comically rude. Inspecting the examples of vocative οὗτος in Greek drama, I shall argue that there is syntactical and pragmatic evidence that outweighs interpreting the demonstrative pronoun οὗτος as the core point for the alleged joke encapsulated in the text, thus settling the matter in favouring the idea that the banter need be in the first summon ὦΦαληρεύς.